Effect of some anions on corrosion behaviour of 1060, 1100 and 5052 aluminium alloys in orthophosphoric acid - Dubey R.S.; Sagar Dubey R.; Upadhya Y.D.; Upadhyay S.N. (My University, 2025)
The effect of chromate, citrate, thiocyanate, tartarate, oxalate and ferrocyanide ions on the corrosion behaviour of 1060, 1100 and 5052 aluminium alloys in 1% orthophosphoric acid has been studied by weight loss technique at 30 and 40 ±0.5°C, whereas corrosion behaviour of 1100 aluminium alloy in the presence of above anions was studied by potentiostatic polarisation technique. It was observed that these anions play a. decisive role in determining the ease with which the above alloys undergo dissolution in orthophosphoric acid. Chromates, oxalates and ferrocyanides worked as corrosion inhibitors, whereas citrates, tartarates and thiocyanates accelerated the corrosion reaction at all the concentrations (0.01-0.2%) investigated. The stability of the surface film formed in the presence of these anions were closely related to the stability constant of metal-chelate complexes.